2014
DOI: 10.1177/1365480214553742
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of child poverty to school education

Abstract: Child poverty is a global issue that affects around half the children in the world; it is inextricably bound to the poverty experienced by their parents and families and has been identified by the United Nations as a human rights issue. Child poverty can be a barrier to children and young people accessing school education or achieving any form of success through participating in school education. This article examines some of the main issues surrounding child poverty and school education and a number of govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
0
22
0
1
Order By: Relevance
“…As a consequence, it seems challenging for many parents to fulfil their various duties of educating children properly as they have to struggle to make ends meet. Unfortunately, some school going children are constrained to join parents to fend for daily bread (Gbollie and Keamu, 2017), contrary to the advice to keep children free from economic activity (Wrigley, 2016), because it is gradually becoming an obstacle to children accessing education (McKinney, 2014). On the other hand, evidence has revealed that socio-economic status of parents and other characteristics plays an important role in promoting quality education and better learning outcomes for students (Fasina, 2011;Center on Education Policy, 2012;Cetin and Taskin, 2016;Pholphirul, 2017).…”
Section: High Poverty Ratementioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, it seems challenging for many parents to fulfil their various duties of educating children properly as they have to struggle to make ends meet. Unfortunately, some school going children are constrained to join parents to fend for daily bread (Gbollie and Keamu, 2017), contrary to the advice to keep children free from economic activity (Wrigley, 2016), because it is gradually becoming an obstacle to children accessing education (McKinney, 2014). On the other hand, evidence has revealed that socio-economic status of parents and other characteristics plays an important role in promoting quality education and better learning outcomes for students (Fasina, 2011;Center on Education Policy, 2012;Cetin and Taskin, 2016;Pholphirul, 2017).…”
Section: High Poverty Ratementioning
confidence: 99%
“…For instance, Colombia's national voucher program is a clear demonstration that a central government can effectively mobilize local government resources and private providers to alleviate constraints to public provision of education (King et al, 1999). Further, government interventions in socially disadvantaged schools in the UK have offered good examples for success (McKinney, 2014). Governments must, therefore, demonstrate fervent political will through budgetary allocation as well as instituting radical and practical steps to promote quality education.…”
Section: Enabling Political Willmentioning
confidence: 99%
“…Unauthorised absence might include unauthorised holidays, unauthorised exceptional domestic circumstances, truancy and 'other' unauthorised absence. Consequently, this leads to difficulty in how levels of absence are calculated and how research and literature are interpreted (Attwood and Croll, 2006;Davies and Lee, 2006;dcsf, 2008;Hilton, 2006;McKinney, 2014;Reid, 2004a;Wilson et al, 2008). The one context that remains within a 'grey' area is absence as a result of exclusion.…”
Section: Definition and Recordingmentioning
confidence: 99%
“…Research has highlighted the connections between poverty, deprivation, low socio-economic class and non-attendance at school (McKinney, 2014;Wilson et al, 2008). Studies have highlighted the relationships among attendance and a number of other general educational factors such as the negative correlation between absence and attainment (Attwood and Croll, 2006;McKinney 2014), although no causal link has been established.…”
Section: Reasonsmentioning
confidence: 99%
See 1 more Smart Citation